Implementasi Program Keluarga Harapan Dalam Pemenuhan Kebutuhan Jangka Pendek Masyarakat Di Desa Bungaejaya Kecamatan Pallangga Kabupaten Gowa - Azis, Ibnu Munsyir; AB, Syamsuddin; Ihsan, Muhammad Alim (Jurnal Publisitas, 2025)
This study aims to examine the implementation of the Family Hope Program (Program Keluarga Harapan/PKH) in fulfilling the short-term needs of the community in Bunga Ejaya Village, Pallangga District, Gowa Regency, as well as to identify the supporting and inhibiting factors in its implementation. The research employs a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. The informants in this study include PKH facilitators, village officials, active beneficiary families (KPM), and non-beneficiary families. The qualitative descriptive method was used to gain a deep understanding of the social phenomena related to the implementation of PKH in the village. Data were analyzed through the stages of data reduction, data presentation, and drawing conclusions, with the validity of the data ensured through triangulation techniques. The findings reveal that the implementation of PKH in Bunga Ejaya Village has been fairly effective in supporting poor families, particularly in meeting their short-term needs in education and health. The aid is distributed as non-cash and is facilitated by PKH facilitators. Key supporting factors include the active role of PKH facilitators, the support of village authorities, and the implementation of Family Capacity Building Meetings (Pertemuan Peningkatan Kemampuan Keluarga/P2K2) as a medium for education and empowerment. However, the program also faces several challenges, such as inaccurate recipient data, low participation of beneficiaries in group activities, and misuse of assistance cards.